Self‐assembly and controlled release behaviour of the water‐insoluble drug nifedipine from electrospun PCL‐based polyurethane nanofibres. (26th February 2013) - Lin, Xiuling; Tang, Dongyan; Du, Haofei
Abstract Objectives Electrospun micro‐ and nanofibres are increasingly being investigated for drug delivery. The components of nanofibres are important influences on the drug release behaviour. The aim of this study was to investigate the self‐assembly and release behaviour of drug from nanofibres. Methods Water‐insoluble drug nifedipine (NIF)‐loaded nanofibres with polymeric carrier of polycaprolactone (PCL)‐based polyurethane (PU) were fabricated by electrospinning. The morphology of the nanofibres and the composite nanofibres with NIF were examined by scanning electron microscopy (SEM). The interactions between NIF and PU were followed by Fourier‐transform infrared spectroscopy, and the elemental composition on the surface of the nanofibres was characterized by X‐ray photoelectron spectroscopy. The release behaviour of NIF from nanofibres was observed by SEM (contacted with or without a drop of ethanol), and demonstrated by UV‐Vis spectroscopy. Key findings In‐vitro drug release studies revealed that a self‐assembly process of NIF particles might be achieved within the body of the nanofibres. The electrospun nanofibre was an ideal drug carrier compared with a spin‐coated film and could achieve controlled release of drug. Conclusions The electrospinning technique could be used to fabricate a polymeric carrier that might have potential applications in the biomedical field.